Validação de um instrumento de avaliação do autocuidado dos pacientes com diabetes mellitus tipo 2 - Anjos, Thaynara Silva dos (2020)
Methodological study, which aimed to validate the instrument for assessing self-care of patients with type 2 diabetes mellitus (INAAP-DM2). The process of constructing this instrument was carried out to make it reliable, accurate and usable. For this, empirical and analytical (statistical) procedures were followed. The first consisted of application planning, application and collection. In the analytical procedures, the tests for dimensionality and precision of the instrument were carried out, with its four steps: Application planning, Application and collection, Dimensionality, Analysis of Items and Precision of the instrument. Data collection took place from February 2018 to June 2019, with 600 patients who met the following inclusion criteria: diagnosis of DM2 and age equal to or above 18 years. Those who had cognitive impairment did not participate in the study. They met the inclusion and exclusion criteria. The interviews were conducted by the author of the present study and two previously trained nurses, using the Sociodemographic Characterization Form, with the following variables: age, gender, city, education, marital status, occupation, family income, time of diagnosis of DM; and and INAAP-DM2, with 131 items, organized into six domains, which are: Seeking and ensuring appropriate multiprofessional assistance; Know and consider the disease and its complications; Adhere to treatment; Know and consider / regulate the discomforts of treatment; Accept the disease and the need for health care; Learning to live with the effects of the disease and the consequences of medical diagnosis and treatment measures on lifestyle. The study was developed in Basic Health Units (UBS's) in the municipalities of Aracaju and Itabaiana, and in the Center for Endocrinology and Diabetes Luciano Barreto Júnior. Diabetes Center of the Sergipe State Pension Institute (IPES). The data obtained through data collection were entered into the Excel program and statistical analyzes and statistical procedures were performed: Factor analysis and internal consistency. The first included the instrument's dimensionality process, including verifying the suitability of the data for factor analysis, through Barttlet's sphericity tests, total KMO and individual KMO; data adequacy, extraction of the number of domains, using the eigenvalues methods, accumulated variance, ScreePlot graph and parallel analysis; and the type of rotation of the factors, through the exploratory factor analysis with Varimax rotation and the verification of the commonality. factor and the type of rotation of the factors. In the second, the Accuracy of the internal consistency instrument was calculated using Cronbach's alpha. In the dimensionality process of the instrument, two items were considered inadequate through the analysis of the individual KMO; another 20 items did not use the same scale, also considered inadequate and separated from the instrument; and 14 items had inadequate factor load and commonality, and were also considered inadequate in the validation process. through the individual KMO test, two items were considered inadequate; 20 items did not use the same scale as the instrument, which was also considered inadequate in the validation process; All 14 items were identified as inadequate by measuring the factor load and / or commonality. Thus, the 34 inappropriate items were excluded, from INAAP-DM2, totaling 95 items in INAAP-DM 2., 95 items. Cronbach's alpha indicated domains ranging from 0.79 (acceptable) to 0.99 (excellent). The total consistency was 0.89 (good), indicating good internal homogeneity of INAAP-DM2. Thus, the instrument proved to be reliable, valid, accurate and ready for use in clinical practice.